HISTORY MATCHING AND PERFORMANCE PREDICTION OF IMPROVED OIL RECOVERY - WATERFLOOD USING BUCKLEY LEVERETT AND CAPACITANCE RESISTANCE MODEL AT Z FIELD - JATI (NIM : 22211316), NUGROHO
Enhanced Oil Recovery Technique may become the only one choice for mature field and Waterflood is the mostlikely method considering the advantage from technology availability and economics. To apply this method in the field it has to be pass project screenings which needs early performance prediction to be able to construct economic analysis and pass all project analysis screening. There are several methods to predict waterflood performance such as Buckley Leverett, Craig Geffen Morse, Dykstra Parson, Stiles dan Bush and Helander which develop based on empirical approach using other site country waterflood success story or based on several ideal assumptions which may create big gap to real condition. The other method which usually comes as the best choice to more credible is Reservoir Simulation, but this method evethough provides more accurate prediction, it consumes much time and effort as well as money thus unpractical to do for early prediction. Z Field is a field that has been producing for more than 40 years and since the last 20 years already applied water injection technology. The application of this technology is quite successful but there is still a chance to optimize the operation by improving water injection process. Field Z do not have a model that is good enough to represent the condition of the reservoir in production during this period. To estimate the production performance of the application is re-used water injection method Buckley-Leverett a fairly simple combination method with Capacitance Resistance model to estimate the effectiveness of water injection reservoir parameters based on a deterministic and analogy from another field and history matching process is carried out with the aktual production on the field. For comparison of the validity of the estimates of the performance of water injection, the authors compared with the empirical methods based on field data from Chevron, and also compared with the curve of the simulation model analysis method. The end result of this study ishowing that BL and CRM methods are capable to provide alternative method to predict performance of the water flood in field Z. The disadvantages of this methods is its simplification with modeling to depict huge actual area and its benefit was this CRM methods will diecrease the impact of Buckley Leverett's assumption of steady state flows.